A Xenograft Model of Vestibular Schwannoma and Hearing Loss. Issue 5 (June 2018) - Dinh, Christine T.; Bracho, Olena; Mei, Christine; Bas, Esperanza; Fernandez-Valle, Cristina; Telischi, Fred; Liu, Xue-Zhong
Abstract : Hypothesis: Microsurgical implantation of mouse merlin-deficient Schwann cells (MD-SC) into the cerebellopontine angle of immunodeficient rats will initiate tumor formation, hearing loss, and vestibular dysfunction. Background: The progress in identifying effective drug therapies for treatment of Neurofibromatosis type II (NF2) is limited by the availability of animal models of VS that develop hearing loss and imbalance. Methods: A microsurgical technique for implanting MD-SCs onto the cochleovestibular nerve of rats was developed. Ten Rowett Nude rats were implanted with either ∼10 5 MD-SCs expressing luciferase (N = 5) or vehicle (N = 5). Rats received bioluminescence imaging, auditory brainstem response testing, and were observed for head tilt every 2 weeks after surgery, for a total of 6 weeks. Tumors were harvested and processed with hematoxylin & eosin staining and immunohistochemistry was performed for S100. Results: Rats implanted with MD-SCs developed significantly higher tumor bioluminescence measurements and hearing threshold shifts at multiple frequencies by the 4th and 6th weeks post-implantation, compared with control rats. Rats implanted with MD-SCs also developed gross tumor. The tumor volume was significantly greater than nerve volumes obtained from rats in the control group. All rats with tumors developed a head tilt, while control rats had no signs of vestibular dysfunction. Tumors demonstrated histological features of schwannoma and express S100. Conclusion: Using this microsurgical technique, this xenograft rat model of VS develops tumors involving the cochleovestibular nerve, shifts in hearing thresholds, and vestibular dysfunction. This animal model can be used to investigate tumor-mediated hearing loss and perform preclinical drug studies for NF2.